ANALISIS KARAKTERISTIK LALU LINTAS DATA INTERNET: APLIKASI WEB VIDEO STREAMING - Jusak, Jusak; Susanto, Pauladie (Journal of Control and Network Systems, 2014)
Along with the development of technology, the need for information is increasing, which is not only in the form of text and picture information are needed but also involves all aspects of multimedia available, for example is video streaming technology. So analysis of QoS for data traffic on web applications video streaming like youtube is need to be done. QoS is the ability to guarantee the provision of resources (resource) and service differentiation in various types of applications which is one of the characteristics Internet data traffic. To determine the quality of web video streaming applications, QoS analysis must be done. delay, jitter, packet loss, and bandwidth utilization is the one of the parameter needed for QoS analysis. This analysis is expected to help network administrators in terms of network design for better future.